2022
DOI: 10.3390/ijerph191610333
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Abdominal Obesity in Peru? A Multilevel Analysis Approach Using a Nationally Representative Survey

Abstract: Abdominal obesity (AO) is a serious public health threat due to its increasing prevalence and effect on the development of various non-communicable diseases. A multilevel analysis of the 2019 Demographic and Family Health Survey (ENDES in Spanish) using the Latin American Diabetes Association (ALAD in Spanish) cut-off points was carried out to evaluate the individual and contextual factors associated with AO in Peru. A total of 30,585 individuals 18 years and older were included in the analysis. The prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…A pattern of abdominal obesity [2] has been shown to increase the health care burden, as previously reported by others [15,16], highlighting the need for encouraging WC measurement even in normal BMI individuals. Fourth, while socioeconomic inequalities among abdominal obesity in the general population have been documented [67], our study suggests that central obesity is currently affecting both extremes of income distribution at an almost similar magnitude among individuals with a normal BMI. Therefore, interventions aimed at reducing the cardiometabolic burden should be tailored to the needs of each income group rather than adopting a "one size fits all" approach.…”
Section: Implications Of the Studymentioning
confidence: 60%
See 2 more Smart Citations
“…A pattern of abdominal obesity [2] has been shown to increase the health care burden, as previously reported by others [15,16], highlighting the need for encouraging WC measurement even in normal BMI individuals. Fourth, while socioeconomic inequalities among abdominal obesity in the general population have been documented [67], our study suggests that central obesity is currently affecting both extremes of income distribution at an almost similar magnitude among individuals with a normal BMI. Therefore, interventions aimed at reducing the cardiometabolic burden should be tailored to the needs of each income group rather than adopting a "one size fits all" approach.…”
Section: Implications Of the Studymentioning
confidence: 60%
“…Our findings showed that both low and high-wealth indexes displayed a risk for abdominal fat accretion. Previous studies have shown that the wealth index is related to central obesity [10,57,[67][68][69]. However, the associated pattern may differ between countries' income levels.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, es de destacar que estos estudios se realizaron en poblaciones de Canadá y China, que difieren étnicamente de la población de nuestro estudio. En respaldo de lo hallado en esta investigación, se ha reportado en población peruana que las mujeres sufren de manera más severa la adiposidad abdominal y las alteraciones metabólicas en comparación con los hombres 14,34 . Más aun, la distribución de grasa corporal varía entre países de Latinoamérica, donde las mujeres peruanas muestran una mayor asociación entre la genómica ancestral nativo americana y la relación cintura-cadera (β=0,014 p<0,001), respecto de sus pares colombianas y chilenas (β=0,005; p=0,003 y β=0,008; p=0,001, respectivamente) 28 .…”
Section: Discussiónunclassified
“…In Peru, the prevalence of obesity among individuals over 15 years old was reported to be 25.8% in 2021 [9]. Abdominal obesity affects over 50% of the adult population in the country [10].…”
Section: Introductionmentioning
confidence: 99%